2012 International Conference on Computing, Electronics and Electrical Technologies (ICCEET) 2012
DOI: 10.1109/icceet.2012.6203749
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent PI control technique in four area Load Frequency Control of interconnected hydro-thermal power system

Abstract: This paper present the Load Frequency Control (LFC) of four area hydrothermal interconnected power system by using Artificial Neural Network (ANN) and conventional PI control approach. Area-l and area-2 consists of thermal reheat power plant whereas area-3 and area-4 consists of hydro power plant. To enhance the performance of PI and Neural controller sliding surface is included. The performances of the controllers are simulated using MATLAB/SIMULINK package. A comparison of and ANN and PI controller based app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The model network is used to predict the effect of controller changes on plant output, which allows the updating of controller parameters. In the study, the frequency deviations, tie-line power deviation and load perturbation of the area are chosen as the neural network controller inputs [21,22]. The outputs of the neural network are the control signals, which are applied to the governors in the area.…”
Section: Narma-l2 Controlmentioning
confidence: 99%
“…The model network is used to predict the effect of controller changes on plant output, which allows the updating of controller parameters. In the study, the frequency deviations, tie-line power deviation and load perturbation of the area are chosen as the neural network controller inputs [21,22]. The outputs of the neural network are the control signals, which are applied to the governors in the area.…”
Section: Narma-l2 Controlmentioning
confidence: 99%
“…The most common controller employed for AGC is based on classical control theory. These conventional controllers can be found in the researches [6][7][8][9]. These studies observed that an integral controller is very simple to implement and can provide zero steady state deviation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, authors in Sahu et al, Sun et al, and Bhatt et al, utilized the system developed in Elgerd and Fosha to study AGC of hydro‐thermal system. Recent research in AGC is mainly focused on multi‐area system whose control areas are 3 or more …”
Section: Introductionmentioning
confidence: 99%